The effects of scolocidal agents on hepatopancreaticobiliary system “An experimenal study” - Burhan EYÜPOĞLU,; Mutlu DOĞANAY,; Erhan REİS,; Yunus Nadi YÜKSEK,; Sezer KULAÇOĞLU,; Nuri Aydın KAMA, (Turkish Journal of Gastroenterology, 2019)
-